2016
DOI: 10.1007/s10072-016-2661-3
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation in drug-resistant epilepsy: the efficacy and adverse effects in a 5-year follow-up study in Iran

Abstract: Drug-resistant epilepsy seems like a different disease compared with easy to control epilepsy, and new strategies are needed to help these patients. Vagus nerve stimulation (VNS) therapy is the most frequently used neurostimulation modality for patients with drug-resistant epilepsy who are not eligible for seizure surgery. In this study, we aimed to evaluate the efficacy and adverse effects of VNS in patients with drug-resistant epilepsy in an open-label, prospective, long-term study in Iran. We selected 48 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…; Pakdaman et al . ). Targeting areas outside the seizure focus has shown some promise (Fisher et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Pakdaman et al . ). Targeting areas outside the seizure focus has shown some promise (Fisher et al .…”
Section: Introductionmentioning
confidence: 97%
“…Cervical vagus nerve stimulation (VNS) is an FDA-approved treatment of drug-resistant epilepsy (Nune et al, 2015) and therapy-refractory major depression (Cristancho et al, 2011). The effectiveness of invasive cervical VNS in patients with drug-resistant epilepsy has been demonstrated repeatedly (Pakdaman et al, 2016;Kawai et al, 2017;Vivas et al, 2017). Furthermore, some initial trials on noninvasive transcutaneous auricular VNS reported promising results (He et al, 2013;Bauer et al, 2016;Barbella et al, 2018), although not all studies demonstrated effectiveness (Song et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These results appear better for temporal lobe surgeries. Table 4 shows neurostimulative techniques like VNS [57,86,120,138,151,157,173] and deep brain stimulation [73], which reflected that the majority of subjects had more than 50% seizure reduction with follow-ups ranging between one to four years. Table 5 showed that the indicators of QOL improved after surgery [37,47,50,59,93,98,101,122,126,134,159,160,165,175,177], except in one study [62].…”
Section: Tunisian Epilepsy Surgery Program At the Charles Nicolle Hosmentioning
confidence: 99%